El vídeo-escultura como elemento de representación de la realidad, dentro del contexto local - Yunga Lluisupa, Diego Felipe (Machala, 2019)
The present work of investigation named “The video - sculpture as element of representation of the reality, inside the local context”, reflects the interest of a problems that happens for unnoticed, but that simultaneously, it is a fundamental base of the history, such it is the case of the conservation of heriditary buildings inside our context. The video as an intangible element represented in a symbolic way with stills of heriditary buildings that are an entity inside the context and the sculpture of a tangible figurative way of a reality that every time in the modern age the architecture, it starts replacing element of representation of identity. The video - sculpture is an artistic redeemed form of significant form, using in a symbolic way elements identitarios with a critical - reflective speech that they are representative inside a context with problems, be already social, political or religious. He function to represent a sculpture that is taken of the hand with the video, is to obtain a wide criterion, on the forms that exist inside the art, as a painting, drawing or installation in the field of the art, this form supports a lineament on the way of expressing a fact or problems that it causes in our reality. This way the art opens to us the door to express and to show with artistic works, that social problem that is still present at present and that are not stagings for lack of interest or because heriditary laws are not fulfilled in our country. With a critical language and simultaneously reflective, this work of qualifications tries to highlight the changes of conservation of heriditary buildings inside the canton the Guabo and simultaneously to reflect the problem that they cause this displacement of heriditary loss. The intention of the present work is to come to the spectator with a metaphorical sense of the reality and symbolized across the video - sculpture, using materials that are representative for the society, since it is the wood that as principal source of identity towards the ancient buildings that nowadays are considered to be a heriditary entity but that pitifully in any cantons and provinces are not an acceptation of conservation, and on the other hand the concrete one that undoubtedly is the evolution of the architecture with major resistance but these buildings remplazan to a heriditary entity that passed several years of this conservation it is completely displaced. This way there are fulfilled the intentions that one raised so that this investigation could be carried out, as the first point, of analysis where it is inferred in the symbolic reflection of the local patrimony of the canton the Guabo, managing to emphasize the importance of the ancient buildings, as the second point, from comprehension who relates the processes of architectural modernization inside the frame of identity in our local and third context of application in producing an artistic work that integrates the video and the sculpture, on the importance of supporting a patrimony of visible identity. It is worth noting that the study in the different fields of art contributes a singularity to the study of a social problem, as well as the theoretical references that today are study of the moment as is the case of modern, postmodern and contemporary art, theoretical components that significantly favor the theoretical basis of the artistic proposal.
El presente trabajo de investigación denominado “El video-escultura como elemento de representación de la realidad, dentro del contexto local”, refleja el interés de una problemática que pasa por desapercibida, pero que a la vez, es base fundamental de la historia, tal es el caso de la conservación de edificaciones patrimoniales dentro de nuestro contexto. El video como un elemento intangible representada de manera simbólica con fotogramas de edificaciones patrimoniales que son un ente dentro del contexto y la escultura de manera tangible figurada de una realidad que cada vez en la era moderna la arquitectura, empieza a sustituir elemento de representación de identidad. El video-escultura es una modalidad artística desempeñada de forma significativa, utilizando de manera simbólica elementos identitarios con un discurso crítico-reflexivo que son representativos dentro de un contexto con problemática, ya sea social, político o religioso. La función de representar una escultura que vaya cogida de la mano con el video, es obtener un criterio amplio, sobre las modalidades que existen dentro del arte, al igual que una pintura, dibujo o instalación en el campo del arte, esta modalidad mantiene un lineamiento sobre la manera de expresar un hecho o problemática que suscita en nuestra realidad. De esta manera el arte nos abre la puerta para expresar y manifestar con obras artísticas, aquel problema social que sigue presente en la actualidad y que no son puestas en escena por falta de interés o porque no se cumplen leyes patrimoniales en nuestro país. Con un lenguaje crítico y a la vez reflexivo, este trabajo de titulación intenta resaltar los cambios de conservación de edificaciones patrimoniales dentro del cantón el Guabo y a la vez reflejar el problema que causan este desplazamiento de pérdida patrimonial. El propósito del presente trabajo es llegar al espectador con un sentido metafórico de la realidad y simbolizada a través del video-escultura, utilizando materiales que son representativos para la sociedad, como es la madera que como principal fuente de identidad hacia las edificaciones antiguas que hoy en día son consideradas como un ente patrimonial pero que lastimosamente en algunos cantones y provincias no son acepción de conservación, y por otro lado el concreto que sin duda alguna es la evolución de la arquitectura con mayor resistencia pero estas edificaciones remplazan a un ente patrimonial que transcurrido varios años de conservación esta sea totalmente desplazada. De esta manera se cumple los propósitos que se planteó para que esta investigación se pudiera llevar a cabo, como primer punto, de análisis donde se infiere en la reflexión simbólica del patrimonio local del cantón el Guabo, logrando destacar la importancia de las edificaciones antiguas, como segundo punto, de comprensión quien relaciona los procesos de modernización arquitectónica dentro del marco de identidad en nuestro contexto local y tercero de aplicación en producir una obra artística que integre el video y la escultura, sobre la importancia de mantener un patrimonio de identidad visible. Vale recalcar que el estudio en los diferentes campos del arte aportan una singularidad al estudio de una problemática social, al igual que las referencias teóricas que hoy en día son estudio del momento como es el caso del arte moderno, posmoderno y contemporáneo, componentes teóricos que favorecen de manera notable a la fundamentación teórica de la propuesta artística.
Keywords: PATRIMONIO; HISTORIA; IDENTIDAD; CONSERVACION